TINJAUAN HISTORIS KONFLIK TANAH ULAYAT PASUKUAN TANJUNG MANGGOPOH DI KABUPATEN AGAM PROVINSI SUMATERA BARAT (1983-2012) - Deka Maita Sandi Deka Maita Sandi (Jurnal Education and Development, 2018)
This study examines the customary land conflicts Suku Tanjung Manggopoh with the aim to reveal the dynamics of conflict escalation, conflict resolution describing, and analyzing the impact of the various conflicts that occurred one after another stretch of land on the Tanjung Manggopoh customary rate. The conflict has been going on for almost three decades since the presence of oil palm investors in 1983 in Nagari Manggopoh. Tribal headland feel the economic and social rights of their customary land disturbed and even danger of being lost, did stimulate resistance and resistance to various parties. Shifting issues of identity conflicts that threatened to be a conflict of economic interests spawned new conflicts, which lead to an escalation and intensity of the conflict and prolong the duration of the conflict. Conflict resolution process to find a resolution, has been done since this conflict is present, either through litigation (court), mediation, and consensus agreement. Longstanding conflict with escalation and high intensity, involving the subject and the object of widespread conflict, and cover a variety of options that have led to the completion of a multi-dimensional excesses in both the social and economic context for each actor involved.